Sosialisasi Pencegahan Perundungan Di Lingkungan Sekolah SDN 1 Songak - Nurmaulia Khotmi; Muhammad Atha Iqbal; Hartini Hartini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Bullying is any physical or psychological violence that is perpetrated repeatedly due to unequal power relations. Repeated frequency of bullying is at least more than once. The purpose of this socialization is to provide information to increase knowledge in all sectors involved in the school environment so as to minimize the occurrence of bullying behavior. This activity was carried out as a face-to-face seminar. In this activity the material presented was